The significance of finerenone as a novel therapeutic option in diabetic kidney disease: a scoping review with emphasis on cardiorenal outcomes of the finerenone phase 3 trials - Arici, Mustafa; Altun, Bulent; Araz, Mustafa; Atmaca, Aysegul; Demir, Tevfik; Ecder, Tevfik; Guz, Galip; Gogas Yavuz, Dilek; Yildiz, Alaattin; Yilmaz, Temel (Frontiers in Medicine, 2024)
This scoping review prepared by endocrinology and nephrology experts aimed to address the significance of finerenone, as a novel therapeutic option, in diabetic kidney disease (DKD), based on the biological prospect of cardiorenal benefit due to non-steroidal mineralocorticoid receptor antagonist (MRA) properties, and the recent evidence from the finerenone phase 3 program clinical trials. The importance of finerenone in slowing DKD progression was critically reviewed in relation to the role of MR overactivation in the pathogenesis of cardiorenal disease and unmet needs in the current practice patterns. The efficacy and safety outcomes of finerenone phase III study program including FIDELIO-DKD, FIGARO-DKD and FIDELITY were presented. Specifically, perspectives on inclusion of patients with preserved estimated glomerular filtration rate (eGFR) or high albuminuria, concomitant use of sodium-glucose co-transporter-2 inhibitor (SGLT2i) or glucagonlike peptide 1 receptor agonist (GLP-1 RA), baseline glycated hemoglobin (HbA1c) level and insulin treatment, clinically meaningful heart failure outcomes and treatment-induced hyperkalemia were addressed. Finerenone has emerged as a new therapeutic agent that slows DKD progression, reduces albuminuria and risk of cardiovascular complications, regardless of the baseline HbA1c levels and concomitant treatments (SGLT2i, GLP-1 RA or insulin) and with a favorable benefit-risk profile. The evolving data on the benefit of SGLT2is and non-steroidal MRAs in slowing or reducing cardiorenal risk seem to provide the opportunity to use these pillars of therapy in the management of DKD, after a long-period of treatment scarcity in this field. Along with recognition of the albuminuria as a powerful marker to detect those patients at high risk of cardiorenal disease, these important developments would likely to impact standard-of-care options in the setting of DKD.